Body composition characteristics and physiological performance tests of junior elite field hockey players according to different playing positions - Bandyopadhyay, A.; Gouriprosad Datta, S.; Dey, K. (Journal of Physical Education and Sport, 2019)
Cellular level body components and their impact on functional performances are still unclear in team sports. We aimed to investigate the position specific characteristics of cellular level body composition and physiological parameters and their inter-relationships among junior elite field hockey players (mean age, 16.2 ±1.87 yrs). One hundred ten (N=110) male field hockey players from different playing positions (Goalkeeper, n=15; Defender, n=39; Midfielder, n=32; Forward, n=24) were evaluated at end of the preparatory phase. Whole body bio-electrical impedance analysis (BIA) was performed using a multi-frequency analyzer (Maltron Bioscan 920-2, Maltron International, Rayleigh, Essex, UK). FFM and TBW were calculated using Asian based prediction equations from manufacturer`s software. Thereafter, maximal isometric grip & back strength, trunk flexibility and 20 meter shuttle test (bleep test; for VO2 max) were conducted followed by standard procedure. One-way ANOVA showed significant differences (p<0.01) in anthropometric indicators and body composition parameters (Glycogen mass, Muscle mass, BCM, ECM: BCM, BCM/FFM%, Total Mineral Mass, TBW, ICW, ICW%, ICW/FFM%) with respect to field positions. Forwards possessed highest levels of active body tissue development and the most efficient cardiovascular systems. Defenders displayed larger body build, while midfielders exhibited significantly (p<0.01) higher values of body cell mass along with superior hydration status relative to body weight. Goalkeepers demonstrated different physical and physiological characteristics from outfielders. Linear regression analysis revealed that both TBW and ICW were the key parameters having significant positive relation (p<0.05) with functional performances. There are qualitative and quantitative alterations between assessed positions and the correct use of these individual differences on behalf of the team can contribute to the sportive success. Loss of ICW but not TBW could be the risk of decreasing upper body strength. Relative BCM, ECM/BCM, BCM/FFM and BCMI needs wide scale application in team sports. Key words:bio-electrical impedance, body cell mass, intra cellular water, physiological performances, young field hockey players.